The march a novel - Doctorow, E. L. 1931-2015 (Random House, 2005)
In 1864, after Union general William Tecumseh Sherman burned Atlanta, he marched his sixty thousand troops east through Georgia to the sea, and then up into the Carolinas. The army fought off Confederate forces and lived off the land, pillaging the Southern plantations, taking cattle and crops for their own, demolishing cities, and accumulating a borne-along population of freed blacks and white refugees until all that remained was the dangerous transient life of the uprooted, the dispossessed, and the triumphant.
Keywords: Sherman's March through the Carolinas - Fiction; Sherman's March to the Sea - Fiction; Geschichte; Sezessionskrieg (1861-1865); Sherman's March through the Carolinas -- Fiction; Sherman's March to the Sea -- Fiction; Georgia - History - Civil War, 1861-1865 - Fiction; South Carolina - History - Civil War, 1861-1865 - Fiction; South Carolina -- History -- Civil War, 1861-1865 -- Fiction; Georgia -- History -- Civil War, 1861-1865 -- Fiction; Historical fiction; War stories; Fiktionale Darstellung